A Nurse-Led Telemonitoring Approach in Diabetes During the COVID-19 Pandemic: Prospective Cohort Study - Stephanie A Noonan; Amanda L Gauld; Maria I Constantino; Margaret J McGill; Timothy L Middleton; Ian D Caterson; Luigi N Fontana; Stephen M Twigg; Ted Wu; Raaj Kishore Biswas; Jencia Wong (JMIR Diabetes)
Abstract BackgroundThe utility of a nurse-led telemonitoring approach (NLTA) is yet to be firmly established in diabetes management. ObjectiveThis study aims to examine the effect of a 12-month proactive NLTA on metabolic and psychological health indices in individuals with diabetes during the COVID-19 pandemic, and to evaluate it as a new diabetes model of care. MethodsThe telemonitoring study group (TSG; n=91) comprised adults who had attended an Australian tertiary hospital diabetes center between January 2019 and March 2020. Telehealth surveillance contact with a diabetes nurse educator was subsequently maintained at approximately 3-month intervals over 12 months. Prospective surveillance measures included glycated hemoglobin A1c1c ResultsThe average participant age was 57.2 (SD 15) years; 63% (129/206) were male, 48% (99/206) had type 1 diabetes, 50% (104/206) had type 2 diabetes, and the mean HbA1c1cP1c1cPP1c1cPP ConclusionsA proactive diabetes NLTA is feasible with positive effects on glycemia and the potential to identify those at psychological risk for targeted intervention. In the context of increasing demand for diabetes-related resources, further study of an NLTA model of care is warranted.